The forming of scenarios of enterprise development on the basis of four-level indicator of sustainable development - Katkova, Natalia; Murashko, Irina (Technology audit and production reserves, 2018)
The object of research is a methodical approach to the scenarios of sustainable development of an enterprise based on the choice of a four-level indicator of sustainable development. One of the most problematic issues is the application of such a methodical approach to determining the level of sustainable development, which would allow the formation of relevant scenarios in interaction with the external environment. For the development of a complex indicator that would take into account the mutual influence of the enterprise and its ecosystem, the study applied a bionomic approach, that is, an approach inherent in the study of biological systems. As a basis for assessing the level of sustainable development of the enterprise, an indicator of ecological capacity is used. It characterizes the limiting loading of a biological species to a habitat or the maximum size of a population of a species that the environment can certainly sustain, provide food, shelter, water, and other necessary benefits. The methodical approach to the formation of scenarios for the enterprise development is improved by developing a four-level indicator of sustainable development, which provides opportunities to determine the ability of certain subsystems of the enterprise to develop, taking into account the availability of internal and external resources. The developed indicator consists of indicators of economic, environmental, social and energy capacity, the characteristics of which are given in the work. Based on the value of the indicator, the proposed scenarios for the sustainable development of an enterprise are a combination of subsystems for which resources are exhausted and which have a supply of resources. To ensure a balanced development of an enterprise, it is possible to redistribute resources between subsystems, for which appropriate measures are determined using the above sustainable development scenarios. In addition, thanks to the developed methodology, it is possible to determine the directions of harmonious coexistence of an enterprise with the external environment, which is the main principle of sustainable development. In comparison with the known approaches, the proposed four-level indicator of sustainable development, as well as scenarios based on it, takes into account the peculiarities of the existence of the enterprise in its ecosystem.